Management of Lateral Semicircular Canal Benign Paroxysmal Positional Vertigo - Zuma e Maia, Francisco; Ramos, Bernardo Faria; Cal, Renato; Brock, Camila Martins; Mangabeira Albernaz, Pedro Luiz; Strupp, Michael (Frontiers in Neurology, 2020)
Benign paroxysmal positional vertigo (BPPV) is the most common cause of peripheral vestibular vertigo. It is caused by free-floating otoconia moving freely in one of the three canals (canalolithiasis) or by otoliths adhered to the cupula (cupulolithiasis). The posterior canal variant of BPPV is the most common canal impairment followed by the lateral canal. Diagnosis of the side affected is critical for successful treatment, therefore, suppressing visual fixation is essential to examination of these patients’ eye movement. On the basis of our experience, we have adopted the Zuma maneuver and the modified Zuma maneuver for both apogeotropic and geotropic variants of LC-BPPV. Knowledge of the anatomy and pathophysiologic mechanisms of the semicircular canals is essential for correct management of these patients and so using the same maneuver may facilitate daily neurotological practice.